Screening Sexually Active Teenagers for Cervical Abnormalities: Its importance for sexually active teenagers - Erdstein, Julius (1991)
Sexually active teenagers are at increased risk of developing cervical abnormalities. It is therefore important to screen them with an annual Pap smear. The techniques of this test are reviewed, as are the importance of sexually transmitted diseases in the development of cytologic abnormalities, the pathophysiology of virus-induced changes, and the terminology of reporting.